2002
DOI: 10.1007/s10237-002-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

Models of cytoskeletal mechanics of adherent cells

Abstract: Adherent cells sense their mechanical environment, which, in turn, regulates their functions. During the past decade, a growing body of evidence has indicated that a deformable, solid-state intracellular structure known as the cytoskeleton (CSK) plays a major role in transmitting and distributing mechanical stresses within the cell as well as in their conversion into a chemical response. Therefore in order to understand mechanical regulation and control of cellular functions, one needs to understand mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 68 publications
4
103
0
1
Order By: Relevance
“…Experiments analyzing the effects of ECM adhesion and mechanical forces on microtubule polymerization in various adherent cells (Joshi et al, 1985;Dennerll et al, 1988;Dennerll et al, 1989;Lamoureux et al, 1990;Mooney et al, 1994;Putnam et al, 1998;Putnam et al, 2001;Kaverina et al, 2002) and a thermodynamic model of microtubule regulation ) support this notion. This may explain why microtubules did not appear to contribute significantly to smooth muscle cell mechanics in a study in which these cells were held under external tension (Obara et al, 2000), whereas in other studies they were found to play an important mechanical role in both smooth muscle cells (Wang et al, 2001;Stamenovic et al, 2002) and cardiac muscle cells (Tagawa et al, 1997).…”
Section: Prestress Is a Major Determinant Of Cell Mechanicsmentioning
confidence: 84%
“…Experiments analyzing the effects of ECM adhesion and mechanical forces on microtubule polymerization in various adherent cells (Joshi et al, 1985;Dennerll et al, 1988;Dennerll et al, 1989;Lamoureux et al, 1990;Mooney et al, 1994;Putnam et al, 1998;Putnam et al, 2001;Kaverina et al, 2002) and a thermodynamic model of microtubule regulation ) support this notion. This may explain why microtubules did not appear to contribute significantly to smooth muscle cell mechanics in a study in which these cells were held under external tension (Obara et al, 2000), whereas in other studies they were found to play an important mechanical role in both smooth muscle cells (Wang et al, 2001;Stamenovic et al, 2002) and cardiac muscle cells (Tagawa et al, 1997).…”
Section: Prestress Is a Major Determinant Of Cell Mechanicsmentioning
confidence: 84%
“…In contrast, while we observed a similar qualitative permeability response to changes in stiffness within endothelial cells cultured on ECM gels, the absolute values of stiffness were very different (cell-cell junctions were disrupted on ECM gels with 150 Pa or 35,000 Pa). This is likely because of difference in the measurement tools we utilized (rheology of cultured gels versus tensile loading of whole lung sections), which can produce different values of mechanical properties based on the area to which force is applied 42 . In addition, our in vitro studies employed only endothelial cells cultured on top of gels composed of one type of ECM component, whereas whole lung ARTICLE contains various cell types grown within three-dimensional ECMs composed of a complex array of insoluble ECM components and bound growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…[92][93][94][95][96][97] It was shown that this approach is particularly well adapted for the description of eukaryotic biological cells. 98 However, the previously listed techniques are usually not able to account for specific interactions between cells, their individual, specific behavior or the active response of cells to external stimuli.…”
Section: Mechanical Properties Of Complex Materials Systemsmentioning
confidence: 99%